Heterogenesis of ends: Herbert Spencer and the Italian economists. Issue 1 (2nd January 2017) - Sunna, Claudia; Mosca, Manuela
Abstract: The influence of Spencer's ideas is now generating a good deal of analysis. The aim of this paper is to highlight the importance of Spencer's work on economic thought. It also analyses the way in which this work was interpreted by the Italian economists. In particular, it investigates the influence of Spencer's theory of evolution on the thought of Pantaleoni (1857–1924) and Nitti (1868–1953). These two representative Italian scholars were on opposite sides for their economic methodology and the issue of government intervention in the economy. The paper clarifies whether their two divergent visions on social change could both be in accordance with Spencer ideas.